Sinalização celular Notch na infecção do trofoblasto extraviloso humano por Toxoplasma gondii - Almeida, Marcos Paulo Oliveira (2023)
Congenital toxoplasmosis results from the maternal fetal acquisition of Toxoplasma gondii and is characterized by physiopathological complications that affect the course of pregnancy. During maternal infection, T. gondii colonizes the placental microenvironment, infecting the extravillous trophoblast through which the parasite can reach the fetal compartments. Extravillous trophoblast cells contribute to gestational success by acting in maternal physiological adaptations for adequate placentation and acceptance of the developing conceptus, being their activities regulated by signal transduction mechanisms in which the Notch signaling pathway stands out, whose action controls cellular events such as proliferation, differentiation, and apoptosis. The contribution of Notch signaling in experimental acute toxoplasmosis was previously investigated through the inhibition of the gamma-secretase enzyme complex, essential for its activation. Since the influence of Notch signaling on the infection of human extravillous trophoblasts by T. gondii remains unexplored, this scenario was the subject of investigation in the present study. For this, HTR-8/SVneo cells, as a model of human extravillous trophoblast, were infected with T. gondii , or not, treated with chemical inhibitors of gamma-secretase, or not, and evaluated for gene expression, parasitism, cytokine production, Notch1 receptor activation and additional mechanisms. In response to infection, HTR-8/SVneo cells showed reductions in the gene expression of DLL4, APP, and IL6R, as well as in the activation of both, the Notch1 receptor and the STAT3 signaling factor. However, treatments with the gamma-secretase inhibitors, DBZ, DAPT and GSI XIV, promoted reductions in cellular parasitism, as well as increased or decreased the secretions of the cytokines IL 6, IL 8 and MIF. Although MIF and IL 6 had increased production by cells in response to infection, these cytokines seem not to be involved in the control of parasitism triggered by gamma-secretase inhibitors. Collectively, it is evident that gamma-secretase is essential for the proliferation of T. gondii in HTR-8/SVneo cells, which respond to infection by reducing the activation of Notch1, suggesting the involvement of Notch signaling pathway in the infection of human extravillous trophoblast by T. gondii.